2022
DOI: 10.1080/03019233.2022.2078261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of slag entrapment process during the end of casting in tundish

Abstract: The slag entrapment process under two different initial conditions during the end of casting in tundish is studied. A 3D multiphase mathematical model was developed to simulate the slag entrapment behaviour. The critical slag entrapment time (t s ) and the corresponding critical slag entrapment height (h cs ) were predicted. The results show the h cs increases, the t s decreases as the casting speed increases, but their relationships are not linear. The influence of casting speed on the h cs in the range of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Liu Ziyu [6] studied the influence of an inner-swirling turbulence inhibitor on the trajectory of inclusions in a tundish and found that an inner-swirling turbulence inhibitor could guide the inclusions to collide with each other in the impact zone of the tundish and transport the inclusions that had collided to the molten steel surface for removal. Li Jian [7] studied the three-phase interaction behavior of molten steel bubbles and inclusions based on the Euler-Lagrange model. The interactions between the steel liquid and bubbles, steel liquid and inclusions, and bubbles and inclusions were considered in the model.…”
Section: Introductionmentioning
confidence: 99%
“…Liu Ziyu [6] studied the influence of an inner-swirling turbulence inhibitor on the trajectory of inclusions in a tundish and found that an inner-swirling turbulence inhibitor could guide the inclusions to collide with each other in the impact zone of the tundish and transport the inclusions that had collided to the molten steel surface for removal. Li Jian [7] studied the three-phase interaction behavior of molten steel bubbles and inclusions based on the Euler-Lagrange model. The interactions between the steel liquid and bubbles, steel liquid and inclusions, and bubbles and inclusions were considered in the model.…”
Section: Introductionmentioning
confidence: 99%